PREVALENCE OF VESICO VAGINAL FISTULA AND COPING STRATEGIES OF WOMEN IN KEBBI STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
Vesico-Vaginal Fistula (VVF) poses a significant challenge for women, particularly in Kebbi State, Nigeria, where a VVF Centre operates to provide surgical repair and healthcare professional training. Despite this, research on VVF prevalence and coping strategies in Kebbi State remains limited, warranting further investigation to address knowledge gaps. This study investigates the prevalence and coping strategies associated with Vesicovaginal Fistula (VVF) among women in Kebbi State. Employing purposive sampling, 49 questionnaires were distributed to women aged 15 years and above. Data analysis involved descriptive statistics, including frequency, and inferential statistics, with Spearman rank correlation analyzing variable associations. Results indicate that the mean age of marriage is 16, with the highest frequencies of married (35.9%) and divorced (27.4%) respondents. Occupation-wise, 33.4% are housewives, revealing low-income earners, especially among casual laborers (28.9%) and farmers (26.9%). VVF prevalence is concentrated among ages 14–19 (30.7%), and overall prevalence is 29.3 per 1000 deliveries. The disease exhibits an increasing trend, with the years 2011-2012 having the least frequency (17%) and a mean score of 5.1. Yearly variations are noted in documented VVF cases from Gesse VVF Centre in Birnin Kebbi (2011-2020). Knowledge of VVF prevalence is highest (100.0%) among age groups 30-34 and 40 and above, contrasting sharply with the smaller proportion (15-30 age group). Coping mechanisms predominantly involve accepting fate. Recommendations include implementing comprehensive health education, targeting girls and women to address early marriage and reproductive health, facilitated by government and health workers.
Keywords: Vesico-Vaginal Fistula (VVF); Coping strategies; Kebbi